Microbial diversity in a submarine carbonate edifice from the serpentinizing hydrothermal system of the Prony Bay (New Caledonia) over a 6-year period - Postec, Anne; Quéméneur, Marianne; Bes, Méline; Mei, Nan; Benaïssa, Fatma; Payri, Claude; Monnin, Christophe; Pelletier, Bernard; Guentas, Linda; Ollivier, Bernard; Gérard, Emmanuelle; Pisapia, Céline; et al. (Frontiers in Microbiology, 2015)
Active carbonate chimneys from the shallow marine serpentinizing Prony Hydrothermal Field were sampled 3 times over a 6 years period at site ST09. Archaeal and bacterial communities composition was investigated using PCR-based methods (clone libraries, Denaturating Gel Gradient Electrophoresis, quantitative PCR) targeting 16S rRNA genes, methyl coenzyme M reductase A and dissimilatory sulfite reductase subunit B genes. Methanosarcinales (Euryarchaeota) and Thaumarchaea were the main archaeal members. The Methanosarcinales, also observed by epifluorescent microscopy and FISH, consisted of two phyotypes that were previously solely detected in two other serpentinitzing ecosystems (The Cedars and Lost City Hydrothermal Field). Surprisingly, members of the hyperthermophilic order Thermococcales were also found which may indicate the presence of a hot subsurface biosphere. The bacterial community mainly consisted of Firmicutes, Chloroflexi, Alpha-, Gamma-, Beta- and Delta-proteobacteria and of the candidate division NPL-UPA2. Members of these taxa were consistently found each year and may therefore represent a stable core of the indigenous bacterial community of the PHF chimneys. Firmicutes isolates representing new bacterial taxa were obtained by cultivation under anaerobic conditions. Our study revealed diverse microbial communities in PHF ST09 related to methane and sulfur compounds that share common populations with other terrestrial or submarine serpentinizing ecosystems.